KANDUNGAN ASAM LEMAK OMEGA 6 PADA KETAM PASIR (Emerita spp) DI PANTAI SELATAN YOGYAKARTA - Dindin Hidayatul Mursyidin (Bioscientiae, 2007)
The objective of this study was to investigate the total content of two omega 6 fatty acids, namely linoleic acid (LA, C18:2n-6) and arachidonic acid (ARA, C20:4n-6), of mole crabs Emerita talpoida and E. Analoga. Samples of mole crabs were collected from intertidal zone of Yogyakarta’s south coast. The omega 6 fatty acids were prepared by in situ transesterification method, and were analyzed by gas chromatography. This study revealed that omega 6 fatty acid of E. talpoida consisted of 9.9% LA and 1.90% ARA, while that of E. analoga consisted of 11.11% LA and 1.83% ARA. It was concluded that the total content of omega 6 fatty acid of E. analoga was higher then that of E. talpoida.